Evaluation of Analytical Performance of Three Blood Glucose Monitoring Systems: System Accuracy, Measurement Repeatability, and Intermediate Measurement Precision. (January 2019) - Pleus, Stefan; Jendrike, Nina; Baumstark, Annette; Mende, Jochen; Haug, Cornelia; Freckmann, Guido
Introduction: Blood glucose monitoring systems (BGMS) should provide sufficient analytical quality to allow adequate therapy for diabetes patients. Besides system accuracy, measurement precision is an important aspect of a BGMS' analytical quality. Methods: Based on ISO 15197:2013/EN ISO 15197:2015, system accuracy, measurement repeatability, and intermediate measurement precision were assessed. ISO 15197:2013 system accuracy criteria require that ⩾95% of individual BGMS' test strip lot results shall fall within ±15 mg/dl or ±15% of corresponding comparison method results (at glucose concentrations <100 mg/dl and ⩾100 mg/dl, respectively), and that ⩾99% of results fall within consensus error grid (CEG) zones A and B. Measurement repeatability was assessed using venous blood samples, whereas intermediate measurement precision was assessed using control solution samples. Standard deviation (SD) and coefficient of variation (CV) were calculated for glucose concentrations <100 mg/dl and ⩾100 mg/dl, respectively. Precision acceptance criteria are not specified by ISO 15197:2013. Results: All three BGMS fulfilled system accuracy criteria with 96% to 98% of individual test strip lot's results falling within the acceptable accuracy limits. All measurement results fell within CEG zones A and B. For measurement repeatability, SD was ⩽3.3 mg/dl, and CV was ⩽3.9% for the investigated BGMS. Assessment of intermediate measurement precision showed SD ⩽1.3 mg/dl and CV ⩽3.0%. Conclusion: All three BGMS fulfilled system accuracy criteria of ISO 15197:2013. In absence of acceptance criteria, precision results were found to be consistent with the manufacturer's labeling of the investigated devices.